Evaluation of adiponectin and TNF-α expression in diabetic patients and its relationship with cardiovascular diseases: Adiponectin and TNF-α expression in diabetic patients - Wei, Xiue; Che, Wenhua; Wang, Qiufeng; Yu, Lili (Cellular and Molecular Biology, 2023)
Diabetes is caused by peripheral insulin resistance and lack of insulin secretion due to the apoptosis of pancreatic beta cells. Tumor necrosis factor alpha (TNF-α), a pro-inflammatory cytokine secreted from the tissue on the insulin signaling pathway, can play a role in causing fat resistance to insulin in type 2 diabetes patients. Adiponectin is a specific protein of adipose tissue. It belongs to the collectin family, which is present in human plasma at a high level and can protect against vascular lesions. Considering the importance of epigenetic changes in the development of multifactorial diseases, this study was conducted to investigate the methylation of TNF-α gene promoter in patients with type diabetes with cardiovascular disease and compare it with diabetic people without cardiovascular disease. Also, the serum concentration of adiponectin was investigated in diabetic patients with and without cardiovascular disease. For this purpose, 95 patients with type 2 diabetes referred to Isfahan Endocrine and Metabolism Research Center were divided into two groups: cardiovascular disease and without cardiovascular disease, based on the angiography results. Serum adiponectin level was measured by the RIA method. In addition to adiponectin, indicators such as FBS, cholesterol, triglycerides, and HDL were also measured in these patients. Then, the promoter region of the TNF-α gene was investigated by bisulfite treatment method, nested PCR, and finally, sequence determination. The results showed that the serum level of adiponectin was higher in diabetic patients without cardiovascular disease than in diabetic patients with cardiovascular disease, but this difference was not statistically significant. Also, no change was observed between men and women in TNF-α gene promoter methylation in diabetic and non-diabetic groups. In general, the decrease in adiponectin concentration in diabetic people can be a factor in causing macroangiopathy, so it can be predicted that the production of recombinant adiponectin can be helpful in the treatment and protection of cardiovascular disease in these patients. Also, it seems that the epigenetic changes of cytokines that play a role in causing insulin resistance in type 2 diabetic patients are not noticeable in the peripheral blood sample. In this regard, other tissues should probably be investigated.